2020
DOI: 10.3847/1538-3881/ab64fa
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Stability of Circumstellar Planets in Binary Systems

Abstract: Planets that orbit only one of the stars in stellar binary systems (i.e., circumstellar) are dynamically constrained to a limited range of orbital parameters and thus understanding conditions on their stability is of great importance in exoplanet searches. We perform ∼700 million N-body simulations to identify how stability regions depend on properties of the binary, as well as, the starting planetary inclination and mean longitude relative to the binary orbit. Moreover, we provide grid interpolation maps and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 101 publications
1
54
0
Order By: Relevance
“…Being expelled from the binary star system is likely not conducive to planetary habitability. Since then, a substantial body of work has been dedicated to investigating the stability of planets in binary star systems (e.g., [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]). Among many other important results, it has been found that stable orbits are possible in the vicinity of circumstellar and circumbinary habitable zones, but that much depends on the exact setup of the systems involved.…”
Section: The Trouble With Two Starsmentioning
confidence: 99%
“…Being expelled from the binary star system is likely not conducive to planetary habitability. Since then, a substantial body of work has been dedicated to investigating the stability of planets in binary star systems (e.g., [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]). Among many other important results, it has been found that stable orbits are possible in the vicinity of circumstellar and circumbinary habitable zones, but that much depends on the exact setup of the systems involved.…”
Section: The Trouble With Two Starsmentioning
confidence: 99%
“…The closer a CBP is to a crit , the higher the amplitudes in a cbp and e cbp become, therefore the change in their amplitudes can vary more significantly, too. Additional research could also explore the role of inclination, which has can cause deviations from the Holman & Wiegert (1999) stability limit (Pilat-Lohinger et al 2003;Quarles et al 2020) and can significantly alter CBP orbital evolution, presumably affecting STEEP and habitability.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that more recent studies by Baraffe et al (2015) and Forbes & Loeb (2019) show that the deuteriumburning limit is 73-74 M Jup , we take the older upper limit of 80 M Jup determined by Saumon & Marley (2008) to be inclusive of higher masses. Quarles et al (2020) find that for a companion to remain bound to its host in a binary star system with a bin , the orbit of the companion must have a/a bin <0.08 for a prograde orbit. For a retrograde orbit, this fraction increases to 0.10.…”
Section: Periodicitymentioning
confidence: 93%